Pengaruh Sukrosa dan Ekstrak Bawang Merah Terhadap Umur Simpan Bunga Krisan Potong - Melkianus Bulan; Ali Hasan; Eko H.A. Juwaningsih (Jurnal Penelitian Pertanian Terapan, 2025)
Cut chrysanthemum flowers (Chrysanthemum indicum L.) were reported to have high economic value but faced a major constraint in the form of a short shelf life (vase life) of only 2-3 days postharvest due to high respiration and transpiration rates. This study aimed to examine the effect of sucrose solution and shallot extract concentrations and their interaction on the shelf life of cut chrysanthemum flowers, as well as to determine the best concentration. The study employed a completely randomized design (CRD) with a 4x4 factorial arrangement and three replications. The first factor was sucrose concentration (0%, 2%, 4%, 6%) and the second factor was shallot extract concentration (0%, 10%, 20%, 30%). The main observed variables included flower freshness, and color changes in flowers, leaves, and stems. The results showed that sucrose application had a highly significant effect (P